Long non-coding RNA LINC00470 in serum derived exosome: a critical regulator for proliferation and autophagy in glioma cells - Ma, Wenjia (Cancer Cell Int, 2021)
BACKGROUND: To explore the mechanism of LINC00470 in serum exosomes from glioma patients regulating the autophagy and proliferation of glioma cells. METHODS: Exosomes were extracted from glioma patients (GBM-exo). Expression of LINC00470 in exosomes was analyzed with the clinicopathological characteristics of glioma patients. Glioma mouse model was established. The effects of LINC00470, miR-580-3p and WEE1 on cell autophagy and proliferation, as well as the activation of PI3K/AKT/mTOR pathway were measured. Dual luciferase reporter assay and RNA immunoprecipitation (RIP) were conducted to validate the binding of LINC00470 and miR-580-3p and of miR-580-3p and WEE1. RESULTS: LINC00470 overexpressed in GBM-exo and associated with disease severity and postoperative survival time of glioma patients. GBM-exo deteriorated tumor progression in nude mice. Cells incubated with GBM-exo or transfected with pcDNA3.1-LINC00470/miR-580-3p inhibitor/pcDNA3.1-WEE1 had less autophagosome, downregulated LC3-II/LC3-I and Beclin1 expression levels and increased expression of p62 as well as strengthened proliferation ability. The PI3K/AKT/mTOR pathway was activated. LINC00470 competitively bound to miR-580-3p with WEE1. CONCLUSION: LINC00470 in GBM-exo can bind to miR-580-3p in glioma cells to regulate WEE1 expression and activate the PI3K/AKT/mTOR pathway, thereby inhibiting autophagy and enhancing the proliferation of glioma cells.